Jangan Memberi Stigma ”Nakal”: Pengaruh pada Prestasi Pendidikan Agama Kristen Siswa Sekolah Dasar - Mita Analisa Sipayung; Romauli Siagian; Tripena Engelina Manullang; Victoria Natalia Simanjuntak; Wenny Ariayani Sipayung; Damayanti Nababan (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
The delinquency of students towards the value of learning achievement in Sekolah Dasar Hidup Baru Batam is a problem posed in this study. Thepurpose of this study is to find out the extent of the relationship of student delinquency to the value of learning achievement in Sekolah Dasar Hidup Baru Batam. The research instruments used are student questionnaires, interviews and observations, the samples used consist of class IV to class V which totals 55 people, sampling techniques using random techniques. In describing the results of the study, the collected data is entered into a table and then processed with data analysis techniques using the product formula of the moment find percent rough numbers. The effect of student delinquency on learning achievement is at more than 50%. The issue of student delinquency is a shared responsibility between the student's guardian and the student's guardian.